Competition policy in infrastructure specific sectors in the Estonian case: entwining of natural monopoly and universal service. Konkurentsipoliitika infrastruktuursetes erandvaldkondades Eesti näitel: loomuliku monopoli ja universaalteenuse põimumine - Sepp, Jüri; Eerma, Diana (Estonian Discussions on Economic Policy, 2012)
There is a growing consensus that the successful development of infrastructure specific sectors depends a lot on the adaption of appropriate public policies and the effective implementation of these policies. The way how regulation is implemented plays an important role in infrastructure development and use. In the article the means of regulating economic policy in Estonia are systematized and evaluated looking at practices regarding both natural monopoly and universal service.